A Cost-Effective Saliva-Based Human Epigenetic Clock Using 10 CpG Sites Identified with the Illumina EPIC 850k Array - Christopher Collins; James Brown; Henry C. Chung (DNA, 2025)
Background/Objectives: DNA methylation profiles have emerged as robust biomarkers of ageing, leading to the development of “epigenetic clocks” that estimate biological age. Most established clocks (e.g., Horvath’s 353-CpG pan-tissue clock and Hannum’s 71-CpG blood clock) require dozens to hundreds of CpG sites. This study presents a novel saliva-specific epigenetic clock built on 10 sites identified from Illumina MethylationEPIC (850 k) array data. Methods: Saliva DNA methylation was analysed from 3408 individuals (age range 15–89 years, 68% male, 32% female, no diagnosed disease) from the Muhdo Health Ltd. dataset (2022–2024), and 10 CpG sites were selected where methylation levels showed the strongest positive correlations with chronological age (Pearson r = 0.48–0.66, p < 1 × 10−20). These CpGs map to genes involved in developmental and metabolic pathways (including ELOVL2, CHGA, OTUD7A, PRLHR, ZYG11A, and GPR158). A linear combination of the 10 methylation sites was used to calculate a “DNA methylation age”. Results: The 10-CpG clock’s predictions were highly correlated with chronological age (r = 0.80, R2 = 0.64), with a mean absolute error of ~5.5 years. Its performance, while slightly less precise than Horvath’s or Hannum’s multi-CpG clocks, is notable given the minimal marker set. It was observed that all 10 clock CpGs undergo age-related hypermethylation. The biological significance of these loci is discussed, along with the potential health and forensic applications of a saliva-based epigenetic age predictor. Conclusions: This study demonstrates that a saliva-specific epigenetic clock using only 10 CpG sites can capture a substantial portion of age-related DNA methylation changes, providing a cost-effective tool for age estimation.